Sinusoidal stimulation on afferent fibers modulates the firing pattern of downstream neurons in rat hippocampus - Wang, Zhao-Xiang; Feng, Zhou-Yan; Zheng, Lv-Piao; Yuan, Yue (Journal of integrative neuroscience, 2020)
Electrical stimulation in the brain is an emerging therapy for treating a wide range of neurological disorders. Although electrical pulses are commonly used in the clinic, other electrical waveforms such as sinusoidal-waves have been investigated to improve the therapeutic efficacy, to reduce the risk of tissue damage induced by stimulation, and to decrease the consumption of electrical energy. However, the effects of sinusoidal stimulation on neuronal activity are still unclear. In the present study, we investigated the neuronal responses to the stimulation of 50-Hz sinusoidal-waves applied on the afferent fibers of the neurons in the hippocampal CA1 region of Sprague-Dawley rat in vivo. Results show that the stimulation increased the firing rate of both pyramidal neurons and interneurons in the downstream region of stimulation. Also, the stimulation eliminated the original theta rhythms (2-5 Hz) in the single-unit activity of the two types of neurons and entrained these neurons to fire at the stimulation rhythm. These results provide new clues for the mechanisms of brain stimulation to suppress the pathological rhythms in the neuronal activity, and for the application of sinusoidal waveforms in brain stimulation therapy.